Pelatihan Perangkat Pembelajaran Abad 21 Berbasis Merdeka Belajar Pada Guru IPS - Bedriati Ibrahim; Suroyo Suroyo; Asril Asril; Piki Setri Pernantah; M. Yogi Riyantama Isjoni (Journal of Community Engagement Research for Sustainability, 2021)
21st-century learning tools based on independent learning on students and relying on the readiness of teachers in preparing learning tools. The purpose of the service is to provide training in the Preparation of Learning Implementation Plans (RPP) by Social Studies cluster teachers in the 21st century learning with the paradigm of independent learning on July 14, 2021, at SMP N 4 Tanah Putih Rokan Hilir. Methods and direct practice and guidance and evaluation in the activities of making learning devices. The result of the training in learning tools is that the teacher masters and is able to write 21st-century skills learning tools, as evidenced by the learning tools in the form of a single sheet lesson plan containing 21st-century skills and the concept of independent learning.